Fatigue analysis of alloy wheel using cornering fatigue test and its weight optimization. (2022) - Shinde, Tarang; Jomde, Amit; Shamkuwar, Sonal; Sollapur, Shrishail; Naikwadi, Vivekanand; Patil, Chetan
Abstract: Aluminium alloys are widely used to manufacture alloy wheels for automobiles. Alloy wheels differ from steel wheels in that they possess high strength to weight ratio, better heat conductivity as well as these wheels have a superior aesthetic look. The present work focusses on the application of corner fatigue test and the simulation of wheel rim in order to reduce its the weight and increase the fatigue life of an aluminium alloy A356 wheel. CATIA V5R19 was used to model the wheel rim, and the fatigue analysis was carried out using Ansys 17. The results of the finite element analysis study indicated that the stress generated in the optimised alloy wheel rim was significantly below the actual yield stress of the aluminium alloy. A mass reduction of 200 gm was achieved through the finite element analysis by proper application of stresses on the wheel rim. The overall weight reduction of 1 kg has contributed to the cost reduction as well as decreased fuel consumption for the automobile.